Analysis of «Dual System» Talent Training Model from the Perspective of Legal Education Reform in the New Era - Xianyang Lu (International Society of Philosophy and Cosmology (ISPC), 2021)
The «dual system» talent training model advocated and designed by the Guangdong University of Petrochemical Technology emphasizes and adheres to that the essence of regular higher education is general education and quality education, rather than vocational education, aiming for training generalpurpose «rough-like» talents for the society on the pre-condition of providing certain professional basic theoretical education. The «dual system» talent training model of the law program is characterized by the «dual nature» at both macro and micro levels. At the macro level, it is mainly manifested in the dual system that attaches importance to the «legal professional quality system + humanistic quality system education,» emphasizing the training of basic legal professional qualities, while valuing the training and development of humanistic qualities and ideological and political concepts, etc. At the micro-level, it is manifested in the dual system of «legal theory knowledge system + legal practice operational knowledge system,» providing basic legal theory education, while strengthening the training of basic legal affairs practical operational skills, so that the students can develop the initial ability to solve simple legal practice problems, thus better resolving the tension between social talent demand and traditional training model. For the purpose of constructing the «dual system talent training model» for legal education, the law program shall adhere to the principle of advancing gradually in due order, focus on scientific setting and arrangement of the elective curriculum system, make the new goal of legal talent training both the starting point and ultimate goal, improve the validity of professional practice courses in the practice sessions, and cultivate students to have a more sound personality and comprehensive knowledge system, meeting the demand for legal talents in the new era.